Peroxisome proliferator-activated receptor gamma as a theragnostic target for mesenchymal-type glioblastoma patients - Hua, Tuyen N. M. (Animo Repository, 2020)
Glioblastomas (GBMs) are characterized by four subtypes, proneural (PN), neural, classical, and mesenchymal (MES) GBMs, and they all have distinct activated signaling pathways. Among the subtypes, PN and MES GBMs show mutually exclusive genetic signatures, and the MES phenotype is, in general, believed to be associated with more aggressive features of GBM: tumor recurrence and drug resistance. Therefore, targeting MES GBMs would improve the overall prognosis of patients with fatal tumors. In this study, we propose peroxisome proliferator-activated receptor gamma (PPARγ) as a potential diagnostic and prognostic biomarker as well as therapeutic target for MES GBM; we used multiple approaches to assess PPARγ, including biostatistics analysis and assessment of preclinical studies. First, we found that PPARγ was exclusively expressed in MES glioblastoma stem cells (GSCs), and ligand activation of endogenous PPARγ suppressed cell growth and stemness in MES GSCs. Further in vivo studies involving orthotopic and heterotopic xenograft mouse models confirmed the therapeutic efficacy of targeting PPARγ; compared to control mice, those that received ligand treatment exhibited longer survival as well as decreased tumor burden. Mechanistically, PPARγ activation suppressed proneural–mesenchymal transition (PMT) by inhibiting the STAT3 signaling pathway. Biostatistical analysis using The Cancer Genomics Atlas (TCGA, n = 206) and REMBRANDT (n = 329) revealed that PPARγ upregulation is linked to poor overall survival and disease-free survival of GBM patients. Analysis was performed on prospective (n = 2) and retrospective (n = 6) GBM patient tissues, and we finally confirmed that PPARγ expression was distinctly upregulated in MES GBM. Collectively, this study provides insight into PPARγ as a potential therapeutic target for patients with MES GBM.